The Role of Urban Local Government in Promoting Green Building Practices at Municipality Level in Bangladesh - Reza, Farhadur (Journal of Multidisciplinary Research Advancements, 2026)
Rapid urbanization rate catalyzes the construction industry throughout the world. Construction industry consumes a significant scale of energy and emits greenhouse gases in the atmosphere and thereby causes climate crisis. In this circumstance, the concept of green building has emerged to ensure sustainable construction and tackle the climate change induced consequences. Through substantial literature review and thematic analysis, this paper attempts to explore the current green building practice, rating system, legal provisions, and governance aspects of green building practices at municipal level in Bangladesh. Findings reveal that a large number of industrial buildings are certified as green building in the industrial zones of mega cities. However, research and practice of green building is hardly found at the municipal level. Policy review indicates that limited green building features have been mentioned in the National Building Code and Environmental Policy and such features are rarely present in the Municipality Act. Besides, Bangladesh is currently following LEED rating system and yet to adopt its own rating system. There is a need for large scale infrastructural development in the municipalities to cope with accelerated urbanization. Hence, green building practice is critical to ensure sustainable urbanization throughout the country. Employing Key Informant Interviews, this study further identifies the major challenges of promoting green building practice and proposes some suggestions to overcome those challenges.